2021
DOI: 10.7554/elife.62709
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted analysis reveals two distinct phases of chloroplast biogenesis during de-etiolation in Arabidopsis

Abstract: Light triggers chloroplast differentiation whereby the etioplast transforms into a photosynthesizing chloroplast and the thylakoid rapidly emerges. However, the sequence of events during chloroplast differentiation remains poorly understood. Using Serial Block Face Scanning Electron Microscopy (SBF-SEM), we generated a series of chloroplast 3D reconstructions during differentiation, revealing chloroplast number and volume and the extent of envelope and thylakoid membrane surfaces. Furthermore, we used quantita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 87 publications
1
56
0
Order By: Relevance
“…De-etiolation studies using tobacco leaves reported that the physical structures of the etioplast prolamellar bodies changed almost immediately when exposed to light, and regularity and size reductions occurred (Armarego-Marriott et al, 2019). Recent work well described in Arabidopsis revealed the chloroplast biogenesis from etioplast into two distinct phases: the "Structure Establishment Phase" for disassembly of the prolamellar body, gradual formation of the thylakoid membrane and initial increase of galactolipids and photosynthesis-related proteins and the "Chloroplast Proliferation Phase" for cell expansion, a linear increase of prokaryotic and eukaryotic galactolipids, photosynthesis-related proteins and increased grana stacking (Pipitone et al, 2021).…”
Section: From Etioplastsmentioning
confidence: 99%
See 1 more Smart Citation
“…De-etiolation studies using tobacco leaves reported that the physical structures of the etioplast prolamellar bodies changed almost immediately when exposed to light, and regularity and size reductions occurred (Armarego-Marriott et al, 2019). Recent work well described in Arabidopsis revealed the chloroplast biogenesis from etioplast into two distinct phases: the "Structure Establishment Phase" for disassembly of the prolamellar body, gradual formation of the thylakoid membrane and initial increase of galactolipids and photosynthesis-related proteins and the "Chloroplast Proliferation Phase" for cell expansion, a linear increase of prokaryotic and eukaryotic galactolipids, photosynthesis-related proteins and increased grana stacking (Pipitone et al, 2021).…”
Section: From Etioplastsmentioning
confidence: 99%
“…They are the transient state of development for chloroplasts and are also considered as a status of austerity because they stop the development of photosynthetic chemicals and structures which are unnecessary in the dark. Within etioplasts, in general, single well-arranged paracrystalline prolamellar body and tubular prothylakoids are formed, and these are interspersed with numerous small plastoglobule with high amounts of carotenoids; mainly lutein and violaxanthin which help to increase the transition to chloroplasts (Park et al, 2002;Rodríguez-Villalón et al, 2009;Solymosi and Schoefs, 2010;Pipitone et al, 2021).…”
Section: Etioplastsmentioning
confidence: 99%
“…Remarkably, this process, referred to as ‘greening’, is estimated to require a two‐fold increase in translation as well as two‐thirds of the cell’s ATP and nitrogen supply (Armarego‐Marriott et al, 2020). Two recent reports have used systems biology approaches to monitor this transition – one in Arabidopsis seedlings during de‐etiolation (Pipitone et al, 2021) and one in adult tobacco plants coming out of an extended dark treatment where etioplasts have formed in leaf tissue (Armarego‐Marriott et al, 2019). Both studies demonstrated that etioplast‐to‐chloroplast development occurs in multiple stages, but is also incredibly rapid.…”
Section: Figmentioning
confidence: 99%
“…Two recent reports have used systems biology approaches to monitor this transitionone in Arabidopsis seedlings during de-etiolation (Pipitone et al, 2021) and one in adult tobacco plants coming out of an extended dark treatment where etioplasts have formed in leaf tissue (Armarego-Marriott et al, 2019). Both studies demonstrated that etioplast-to-chloroplast development occurs in multiple stages, but is also incredibly rapid.…”
mentioning
confidence: 99%
“…An accurate understanding of the granum structure enables the determination of reliable measuring protocols necessary to provide comparable results obtained by different researchers. Detailed analysis of grana structure provides important information about the thylakoid membrane remodeling forced by plant ontogenesis (Kowalewska et al, 2016;Armarego-Marriott et al, 2019;Pipitone et al, 2021), light intensity and quality (Rozak et al, 2002;Yamamoto et al, 2014;Demmig-Adams et al, 2015;Schumann et al, 2017;Flannery et al, 2021), and other environmental factors (Fq et al, 2012;Jiang et al, 2017;Chen et al, 2018a;Zechmann, 2019;Mazur et al, 2020). However, structural analysis indirectly indicates the organization and efficiency of the photosynthetic light reaction machinery (Pribil et al, 2018;Mazur et al, 2019;Wood et al, 2019;Hepworth et al, 2021) and photonic effects in the thylakoid network (Capretti et al, 2019).…”
mentioning
confidence: 99%